Truth Claims Across Media - Schirrmacher, Beate; Mousavi, Nafiseh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book offers an intermedial approach to truthful communication. Bringing together a wide range of media types and interactions from a transmedial perspective, the volume maps out how truth claims are made in different contexts, and how different media promise to create a truthful perception of the social world. The flexible communicative possibilities of digital technology have a significant impact on our perception of truth and truthfulness of communication. Bot accounts, deep fake videos, or AI technology draw attention to how reliable communication is destabilized and questioned. In this unstable climate, binaries such as true/false, authentic/fake and fiction/facts are difficult to apply. Instead, it is crucial to investigate how media products construct truthfulness in different ways. The volume brings together various media types and contexts such as press conferences, documentaries and mockumentaries, images in magazines and on social media, horror movies, biopics, and educational games and explores how truth claims, authenticity discourses, and knowledge communication are established and how they collide, merge, or are confused. Beate Schirrmacher is an Associate Professor in Comparative Literature at Linnaeus University, Sweden. She is the head of the International Society of Intermedial Studies, and the co-editor of Intermedial Studies: An Introduction to Meaning across Media. Her research focuses on truth claims and narratives in journalism and the relations of music and literature. Nafiseh Mousavi holds a PhD in comparative literature and teaches intermedial studies at Lund University, Sweden. Her research focuses on the intersections of intermediality, migration, and memory practices. .
Chapter 1. Introduction: The Dynamics of Truthfulness and Media -- Part I Factual Evidence and Coherence in Knowledge Communication -- Chapter 2. A Story Too Good to Be True: The Manipulation of Truth Claims in Faked News -- Chapter 3. The Montage of the National Past: Polish Right-Wing Illustrated Press and the Abuse of History -- Chapter 4. Trustworthiness in the Swedish Strategies for Covid-19 in Recorded Press Conferences from the Public Health Agency of Sweden -- Part II Personal Quests for Empirical Truth: Testimony and Media Hybridity -- Chapter 5. Unveiling Truth and Truthfulness in the Graphic Memoir Heimat -- Chapter 6. Cameras, Pencils, Traumas: Drawn Images in and as Documentary Practice -- Part III Fact and Fake across Media Types -- Chapter 7. Fictionality as a Rhetorical Tool in Political Mockumentary Films: The Interplay of Fictionality and Factuality in C.S.A.: The Confederate States of America -- Chapter 8. Clemens J. Setz on Bursting the Reader$1 (Bs Reality Bubble -- Chapter 9. (3z(BAn Occasionally True Story(3y(B: Biofiction, Authenticity and Fictionality in The Great (2020) -- Chapter 10. Impure Realism, Pure Eventness, and Horror Cinema in the Post-truth Era: A Case Study of One Cut of the Dead -- Part IV Interaction, Trust, and Truthfulness on Social Media -- Chapter 11. Developing Misinformation Immunity in a Post-Truth World: Human Computer Interaction for Data Literacy -- Chapter 12. When the Post-Truth Devil Hides in the Details: A Digital Ethnography of Virtual Anti-Vaccination Groups in Lithuania -- Chapter 13. Towards a Grammar of Manipulated Photographs: The Social Semiotics of Digital Photo Manipulation.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Digital media; Intermediality; Digital and New Media; Intermediality